Marketing across cultures - Usunier, Jean-Claude (Europe : Prentice Hall, 1996)
This work deals with international marketing and is intended to help readers develop their intercultural skills. The cultural variable is of prime importance in that it impacts upon communication, business, negotiation, consumer needs and attitudes, and finally the design and implementation of marketing strategies. The book proceeds by comparing national marketing systems and local commercial customs in various countries, emphasizing what is country-specific and what is universal. There follows an exploration of the interaction between business people, buyers and sellers who have different national/cultural backgrounds. Written from a European perspective, this second edition contains more on cultural issues, especially religion and values, and includes new chapters on cross-cultural consumer behaviour, and the cultural aspects of religious integration
Includes bibliographical references and indexes.
Keywords: Marketing -- Cross-cultural studies; International business enterprises -- Social aspects; Marketing; Business